HYPERCOORDINATED ORGANOSELENIUM COMPOUNDS WITH O→Se INTRAMOLECULAR INTERACTIONS - POP, Alexandra; POPA, Roxana Alexandra; SILVESTRU, Cristian; SILVESTRU, Anca (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Single-crystal X-ray diffraction studies revealed a monomeric structure with O→Se intramolecular coordination in compounds [Me2C(OH)CH2][2-(Me2NCH2)C6H4]Se (1) and [2-(O=CH)C6H4]Se[S(S)P(OPri)2] (2). These interactions result in distorted T-shaped coordination geometries around selenium in both compounds and prevent a C,N-chelating behavior of the 2-(Me2NCH2)C6H4 group in 1 and a bidentate behaviour of the dithiophosphorus ligand in 2, respectively.